E-Marketing Audit sebagai Tools Pengendalian Usaha pada UKM di Kota Malang - Resanti Lestari; Rudy Wahyono; Aris Siswati (Jurnal Manajemen dan Kewirausahaan, 2020)
This study aims to: 1) design an information system related to marketing audits, especially marketing functions in the form of an E-Marketing Audit model design based on conceptual studies and empirical exploration, 2) develop a web-based information system, and 3) apply the E-Marketing Audit model for SMEs Malang City. This study uses a qualitative research methods. Qualitative research is conducted to define the need for marketing audits using depth in interviews to enrich the development of conceptual models and applicable systems.  While system development uses the waterfall SDLC model development method. This method is a sequential or sequential approach to the software life flow starting from analysis, design, coding, testing and implementation. The object of research is an SME in Malang City, observation activities are conducted on 20 SMEs in Malang City and depth interview is conducted with 3 SMEs who represent the characteristics needed in this research. This activity is aimed at elaborating on the need for the formation of a model as a basis for designing an applicable model of E-Marketing audit for SMEs in Malang. The results obtained are in the form of a web-based marketing audit system that is ready to be used by prospective users (SMEs). The resulting marketing audit system features recording product sales, recording of production costs and product price variations, recording sales channels (if an SME uses more than 1 distribution channel), auditing promotional activities by connecting the system to social media and measuring its impact. https://doi.org/10.26905/jmdk.v8i2.5097